2022
DOI: 10.1111/ajt.17026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different urinary tract infection phenotypes within the first year post-transplant on renal allograft outcomes

Abstract: In this study, we investigated the clinical impact of different urinary tract infection (UTI) phenotypes occurring within the first year after renal transplantation. The population included 2368 transplantations having 2363 UTI events. Patients were categorized into four groups based on their compiled UTI events observed within the first year after transplantation: (i) no colonization or UTI (n = 1404; 59%), (ii) colonization only (n = 353; 15%), (iii) occasional UTI with 1-2 episodes (n = 456; 19%), and (iv) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 38 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…The risk of death from infection is 32 times higher for those who received KT, and mortality due to sepsis is 20-fold higher than that in the general public [ 3 , 16 ]. Several studies have reported that postoperative UTIs in patients undergoing KT are important causes of acute graft dysfunction if not adequately treated [ 2 , 7 , 14 , 17 ]. In addition, recipients who developed rejection are more prone to UTI, and recurrent UTIs in KT recipients are associated with an increased risk of fibrosis of the renal allograft [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of death from infection is 32 times higher for those who received KT, and mortality due to sepsis is 20-fold higher than that in the general public [ 3 , 16 ]. Several studies have reported that postoperative UTIs in patients undergoing KT are important causes of acute graft dysfunction if not adequately treated [ 2 , 7 , 14 , 17 ]. In addition, recipients who developed rejection are more prone to UTI, and recurrent UTIs in KT recipients are associated with an increased risk of fibrosis of the renal allograft [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urine analyses and cultures were performed at each consultation after KT. UTI was defined as the existence of bacterial and/or fungal infection in urine with ≥10 5 colony-forming units/mL with or without urinary and/or systemic symptoms of UTI [ 14 ]. Asymptomatic bacteriuria was defined as the absence of symptoms associated with UTI and a positive urine culture.…”
Section: Methodsmentioning
confidence: 99%
“…The epidemiology and outcomes of transplant infections have been characterized in detail in several publications of the STCS. Some studies have described the general epidemiology of infection in all patients included in the cohort, 4 whereas others have focused on a specific type of pathogen (e.g., cytomegalovirus and other herpesviruses, 5,6 Aspergillus , 7 Clostridioides difficile 8 ) or on a specific syndrome (e.g., food‐borne infection, 9 urinary tract infection 10 ). In addition to the scientific value, these publications have a pivotal role in quantifying the burden of disease associated with infection, in describing local trends on the epidemiology of specific infections, and in identifying potential unexpected infectious diseases concerns in a particular center 11 .…”
Section: Epidemiology Of Transplant‐infectious Diseases In Switzerlandmentioning
confidence: 99%
“…The reported prevalence of ASB varies greatly depending on the study, population enrolled, time elapsed since KTx, use of antibiotic prophylaxis and length of follow-up from 3% to 50% [ 8 , 10 ]. ASB is the most frequent clinical phenotype in the first month after KTx, after which symptomatic infections predominate and the relative proportion of ASB decreases [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%